CREATIVE POTENTIAL OF STUDENTS OF A TECHNICAL UNIVERSITY: DEVELOPMENT OPPORTUNITIES - Махинько, Валерій; Махинько, Людмила; Хархалуп, Михайло (SWorldJournal, 2023)
Modern post-industrial society requires appropriate specialists for its efficient functioning. But they must have not only technical skills in their profession but also developed abilities for technical creation. After all, technical progress is impossib